THE CURRENT STATE AND POSSIBLE SOLUTIONS OF WATER AND POWER PROBLEMS IS CENTRAL - THE ASIAN REGION - L. Yu. Gusev (Vestnik MGIMO-Universiteta)
The article deals with a current situation of water problems of Central Asia. It is noted that problems in this sphere began in the thirties the 20th century. The author specifies that in long-term prospect the problem of water management in the Central Asian region will become aggravated because of high rates of an increase in population. It is spoken about contradictions between the states in the hydro-electric sphere, noted that the states of Central Asia, most likely, can't develop new approach to joint development of an energy potential of the region, and the mechanism of management of hydro-electric resources which would answer the political, economic and ecological goals of each state. It is said that now, each of the countries of the Central Asian region seeks to solve a water problem unilaterally, favorable only to it. The author defines the main contradiction that interests of the countries users water resources don't coincide. Some countries want to use water in an irrigational mode, others – in a power mode. As a result of it also there is a conflict situation. It is specified that in an irrigational mode water resources need to be spent in summer, and in a power operating mode the main water consumption is used in winter. It is noted in article that as in the territory of Kazakhstan, Uzbekistan and Turkmenistan lands generally for agriculture are located, these countries being in lower reaches, are interested to use water resources in an irrigational mode. As for interests of Kyrgyzstan and Tajikistan located in highlands and having only limited reserves of oil and gas, they mostly use water in a power mode. The special attention in article is paid to hydroenergy resources of Tajikistan and Kyrgyzstan because these states possess their considerable stocks. Possible measures for stabilization of the situation for this problem are considered. On this basis some recommendations for Russia’s policy in this question are formulated.